Hubungan Karakteristik Perawat dengan Lama Rawat Pasien di Ruang Gawat Darurat Rumah Sakit dr. Slamet Garut - Zahara Farhan; Devi Ratnasari; Buyung Reza Muhammad; Eti Suliyawati; Eva Daniati (Postgraduate, University of Mataram, 2025)
Fast and precise service must be done in handling patients in the emergency room. Services in the emergency room can be hampered if there is a condition of accumulation of patients in the emergency room which is usually caused by an imbalance between the number of patients entering the emergency room with the number of nurses. This study aims to determine the relationship between nurse characteristics and length of stay (LOS) in the emergency department of dr. Slamet Garut Regional General Hospital. This research design uses cross sectional with a sample size of 50 people. The sampling technique uses total sampling. Data collection will use a questionnaire. Data analysis of gender variables (nominal) and length of stay (ordinal) uses the chi-square test, while for variables of age, education level, length of work, (ordinal) and length of stay (ordinal) uses the spearman-rho test. The research location will be carried out in the emergency department of General Hospital dr. Slamet Garut for 2 months from August to September 2025. The results of the study show that no relationship between the educational level of nurses and the length of stay of patients in the emergency room with a p-value of 0.40, no relationship between the gender of nurses and the length of stay of patients with a p-value of 0.94, no relationship between the age of nurses and the length of stay of patients with a p-value of 0.21, and no relationship between the work experience of nurses and the length of stay of patients with a p-value of 0.91. The high workload of nurses can lead to fatigue, loss of concentration, narrowed focus and attention, which impacts the speed and accuracy of nurses in performing emergency procedures on patients, thereby increasing the length of stay of patients in the emergency room. Overall, there was no correlation between the age, gender, educational level, and work experience of nurses and the length of stay of patients in the emergency room at dr. Slamet Garut Hospital.